STATISTICS OF GYNECOLOGICAL MALIGNANCIES - Ye. M. Aksel (Опухоли женской репродуктивной системы, 2014)
The paper analyzes data on the state-of-the-art of oncological care given to patients with gynecological cancer, considers differences in morbidity rates between individual population groups and regions, and compares the maximum and minimum cancer morbidity rates among different populations.